District planning and economic development - Degaonkar, C.K. (Jaipur, 1990)
The book contains a comprehensive survey of the existing literature on planning, development and the regional growth process. The objectives, scope and methodology of a district plan are dealt within detail to give a clear picture about the tasks involved in planning at the district level. The problems of finance, integration and implementation are also discussed at length. It may therefore serve the interests of the policy makers, adminis trators and the students of Economics and Regional Planning.
Keywords: Economic development